A Comprehensive Framework for Drainage, Dewatering and Treatment Technologies in Acid Mine Drainage Control - Jarwinda Jarwinda; Andrew Andrew; Tiorivaldi Tiorivaldi; M. Khalid Al Hijri; Rully Ernando; Hafid Zul Hakim; Alfath Zain; Leta Lestari; Divia Lestari; Ellyas Alga Nainggolan; Dedy Anwar; Dodi Devitriano; Hutwan Syarifuddin; Anis Tatik Maryani (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2026)
Acid mine drainage (AMD) represents a long-term environmental challenge originating from the oxidation of sulfide minerals and mobilization of dissolved metals into surrounding water systems. This study developed a comprehensive framework for AMD control that integrates drainage prevention strategies, hydraulic engineering, active and passive treatment technologies, monitoring systems, and sustainability principles into a unified approach. The framework synthesizes advances in geochemical mine planning, diversion and dewatering systems, hybrid chemical–biological treatment processes, and emerging technologies, including microbial electrochemical systems, selective metal recovery, and digital twins. A life cycle assessment was applied to evaluate environmental and economic trade-offs, emphasizing the potential for circular economy strategies that convert AMD byproducts into valuable resources. This review highlights the importance of adaptive management supported by real-time monitoring, stakeholder involvement, and robust regulatory structures. By connecting technological innovation with policy and ecological restoration objectives, the proposed framework supports resilient AMD control over the entire mine lifecycle and contributes to sustainable post-closure water management.